2002
DOI: 10.1038/sj.gene.6363920
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of interleukin-10 production by genetic and environmental factors – a twin study

Abstract: Interleukin-10 (IL-10) has a critical role in the regulation of immune responses. The relative contribution of genetic and environmental factors to IL-10 production is under debate. We performed a twin study in 246 monozygotic and dizygotic twins to assess the heritability of IL-10 production after LPS stimulation in whole blood. In addition, the influence of promoter single nucleotide polymorphisms (À1082, À819 and À592) on transcriptional activity and their binding to nuclear factors was studied in luciferas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
177
1
5

Year Published

2003
2003
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(186 citation statements)
references
References 34 publications
3
177
1
5
Order By: Relevance
“…Whereas the genetic influence on LPS-induced IL-10 production was estimated to explain a proportion of variance of 0.5 and a heritability of 0.75, 10,28 we found a proportion of variance explained (r 2 of QTDT) as small as 0.02 for the influence of the ATA haplotype on antigen-reactive proliferation. The reason may well be that, in contrast to the direct effect of LPS on macrophages, the effect of an antigen on IL-10 production by T cells is influenced by a number of variables, including antigen presentation, costimulatory activities, numbers of antigen-reactive Tr1 cells, and possible influences of concomitant infections.…”
Section: Discussionmentioning
confidence: 51%
“…Whereas the genetic influence on LPS-induced IL-10 production was estimated to explain a proportion of variance of 0.5 and a heritability of 0.75, 10,28 we found a proportion of variance explained (r 2 of QTDT) as small as 0.02 for the influence of the ATA haplotype on antigen-reactive proliferation. The reason may well be that, in contrast to the direct effect of LPS on macrophages, the effect of an antigen on IL-10 production by T cells is influenced by a number of variables, including antigen presentation, costimulatory activities, numbers of antigen-reactive Tr1 cells, and possible influences of concomitant infections.…”
Section: Discussionmentioning
confidence: 51%
“…24 A recent paper suggested that the production of IL10 is probably more complicated than originally thought, as environmental factors may work along with genetic factors to play a role in affecting IL10 expression. 86 This complexity underlying IL10 expression may explain some of the discrepancies between these studies. A couple of studies have examined the role of TNF variants and the response to therapy.…”
Section: Susceptibility To Persistent Hcv Infectionmentioning
confidence: 99%
“…19,20 Changes in the IL-10 gene expression were suggested to be mainly transcriptional and several factor-binding sites that might be involved in the regulation of IL-10 were identified in the IL-10 promoter. [21][22][23][24] The À1087 single nucleotide polymorphism (SNP) is located in one of these sites that was associated with differences in IL-10 gene expression [25][26][27] and the GG genotype of the À1087 SNP was found to be associated with high levels of IL-10 production. 26,27 Recently, we reported that the PU.1, Spi-B and Sp1transcription factors bound to the À1087 SNP in Bcells.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] The À1087 single nucleotide polymorphism (SNP) is located in one of these sites that was associated with differences in IL-10 gene expression [25][26][27] and the GG genotype of the À1087 SNP was found to be associated with high levels of IL-10 production. 26,27 Recently, we reported that the PU.1, Spi-B and Sp1transcription factors bound to the À1087 SNP in Bcells. 28 Although PU.1 and Spi-B bound to both the G and A allele, Sp1 bound only to the G allele and thereby promoted an increase in promoter activity.…”
Section: Introductionmentioning
confidence: 99%